Influence of hydrodynamic regimes on mixing of waters of confluent rivers - Lyubimova, Tat’yana Petrovna; Lepikhin, Anatoliy Pavlovich; Parshakova, Yanina Nikolayevna; Gualtieri, Carlo; Lane, Stuart Nicholas; Roux, Bernard (Computational Continuum Mechanics, 2018)
At present, a significant weakening of the intensity of transverse mixing at the confluence of large rivers, which is observed in a number of cases, is widely discussed. Since the observed features of the confluence of large watercourses are not only of research interest, but also of significant economic importance associated with the characteristics of water management at these water bodies, a large number of works are devoted to their study. To explain this interesting phenomenon important from the point of view of ecology, a wide range of hypotheses is proposed, up to the negation of turbulence in rivers. One of the possible mechanisms for explaining the “suppression” of transversal mixing can be the presence of transverse circulation, manifested as Prandtl’s secondary flows of second kind. The characteristic velocity of these circulation flows is very small and difficult to measure directly, but they can significantly complicate the transverse mixing of the flow. In the present work, this hypothesis is tested on the basis of computational experiments in a three-dimensional formulation, performed for the configuration modeling of the Kama river at its confluence with the Vishera river. Calculations have shown that, at sufficiently large flow rates the two waters practically do not mix in the horizontal direction throughout the depth over long distances from the confluence. The reason for the weakening of transversal mixing is the formation of a two-vortex flow in the cross section below the confluence place. The fluid motion in vortices is such that, near the free surface, the fluid moves from the banks to the middle of the river.